Impact of Heat and Pressure Processing Treatments on the Digestibility of Peanut, Hazelnut, Pistachio and Cashew Allergens - Claudia Arribas; Africa Sanchiz; Mercedes M. Pedrosa; Selene Perez-Garcia; Rosario Linacero; Carmen Cuadrado (Foods)
Food processing can alter protein biochemical properties, impacting immunoreactivity and allergenicity. A key feature of food allergens is their resistance to enzymatic digestion, particularly by pepsin and trypsin. This study compares the digestomes of raw and heat- and/or pressure-treated peanuts, hazelnuts, pistachios and cashews using the INFOGEST harmonized digestion protocol and analyzing their IgE-binding capacity through in vitro methods. Protein patterns from controls and digestomes were resolved by SDS-PAGE and tested with sera from allergic patients, confirmed by competitive ELISA for hazelnuts and peanuts. The results indicate that processing methods differently affect the gastrointestinal (GI) digestion of these allergens. Simulated GI digestion caused a significant destruction of protein structures, reducing but not eliminating IgE reactivity for all four nuts. Boiling for 60 min did not change the SDS-PAGE profiles, but it did stimulate enzymatic activity, decreasing IgE binding capacity. In contrast, applying heat and pressure led to a nearly complete inhibition of allergenic potential during simulated digestion. These findings suggest that employing intense food processing techniques and investigating the gastrointestinal effects of highly allergenic nuts could be crucial steps toward developing new hypoallergenic formulations.